Effect Of Adding Moringa Leaf Extract (Moringa oliefera) And Kencur (Kaempferia galanga) in Feed On Improving The Growth Performance Of Catfish (Clarias Sp.) - Riana Rahmawati; Fittrie Meyllianawaty Pratiwy; Asep Agus Handaka Suryana; Roffi Grandiosa Herman (Universitas Islam Lamongan, 2024)
The purpose of this study is to determine the influence and determine the optimal dose of moringa leaf extract and kencur in feed on the growth performance of catfish seeds. This research was carried out at the Aquaculture Laboratory, Faculty of Fisheries and Marine Sciences Padjadjaran University from February to March 2024. Sampling in this study used an experimental method using a Complete Random Design (RAL), the growth data obtained was analyzed using the analysis of the F test variety fingerprint (ANOVA / Analysis of Varience) and for the water quality data was analyzed descriptively. The results of this study, namely the addition of 150 mg/kg of moringa leaf extract and 250 mg/kg of kencur extract to feed had an effect on improving the growth performance of catfish seeds which was more optimal than other treatments, as shown by an increase in the percentage of absolute length growth (4.2 cm), absolute weight (57.58 g), SGR (3.80%), FCR (1.44%), EPP (68.90%), and SR (100%). The water quality values during fish rearing are in the optimal range including temperature (27.5-28.3°C), pH (7.0-7.5), and DO (5.2-7.5 mg/L).